2017
DOI: 10.1161/jaha.116.005341
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Evaluation of the Impact of Pokémon GO on Physical Activity

Abstract: BackgroundPokémon GO is a location‐based augmented reality game. Using GPS and the camera on a smartphone, the game requires players to travel in real world to capture animated creatures, called Pokémon. We examined the impact of Pokémon GO on physical activity (PA).Methods and ResultsA pre‐post observational study of 167 Pokémon GO players who were self‐enrolled through recruitment flyers or online social media was performed. Participants were instructed to provide screenshots of their step counts recorded by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 9 publications
4
49
1
Order By: Relevance
“…According to the qualitative ndings, this was more pronounced for o cers and staff who were less active at the beginning of the study, and lacking in intrinsic motivation. Similar ndings have been reported in previous mHealth studies, where less active subgroups have shown the largest increases in PA (46,47). This nding is encouraging in that less active individuals are likely to realise the greatest health gains from increasing their PA levels (48).…”
Section: Discussionsupporting
confidence: 88%
“…According to the qualitative ndings, this was more pronounced for o cers and staff who were less active at the beginning of the study, and lacking in intrinsic motivation. Similar ndings have been reported in previous mHealth studies, where less active subgroups have shown the largest increases in PA (46,47). This nding is encouraging in that less active individuals are likely to realise the greatest health gains from increasing their PA levels (48).…”
Section: Discussionsupporting
confidence: 88%
“…One study estimated that Pokémon Go users' have accrued 144 billion steps in the US 3 . Likewise, Xian et al 4 reported an increase in physical activity from pre-to post-launch and that the number of users' reaching the ≥10,000 daily steps recommendation significantly increased from 15.3% to 27.5%. They also reported the greatest increase in physical activity for those using the application most often, people who are overweight or with obesity and those with the lowest pre-launch physical activity levels.…”
Section: Objectivementioning
confidence: 95%
“…Supplementing the real world with computer imagery allows players to become immersed in the game, requiring them to be physically active to capture and hatch new Pokémon [ 7 ]. Some studies suggest that Pokémon GO increases physical activity and discourages sedentary behavior among adults [ 8 - 11 ]. However, another study showed that although the number of steps increased at the beginning, it gradually decreased and returned to previous levels 9 weeks after downloading the game [ 12 ].…”
Section: Introductionmentioning
confidence: 99%